The influence of privacy regulation on urban Malay families living in terrace housing - Hashim, Ahmad Hariza; Abdul Rahim, Zaiton (Massachusetts Institute of Technology (MIT, 2008)
This paper reports on behavioral norms and territoriality as part of behavioral and environmental mechanisms used to regulate privacy among urban Malay families living in terrace housing. In-depth interview was employed involving 11 case studies of Malay families living in three-bedroom two-storey terrace housings in the urban areas. Findings indicate that while most of the behavioral norms employed to regulate privacy are consistent with Malay cultural norms and religious belief, there are a few which are not consistent due to the constraint of terrace housing. Defined territory and the need to respect the neighbors’ privacy are found to indirectly affect community intimacy among Malay families living in terrace housings.